A RARE PRESENTATION OF MYCOPHENOLATE MOFETIL-INDUCED SEGMENTAL COLITIS MASQUERADING AS ISCHEMIC COLITIS. (26th January 2023) - Miranda, Clive; Ali, Murad; Ayaz, Muddasir; Akbar, Matthew; Soofi, Yousef; Ismail, Mayada
Abstract: Mycophenolate mofetil (MMOF) is an immunosuppressive pro-drug commonly used to prevent rejection in recipients of solid organ transplants. It is hepatically converted to mycophenolic acid which then acts to reversibly inhibit inosine monophosphate dehydrogenase, thereby preventing B and T lymphocyte proliferation, B cell antibody formation, and leukocyte recruitment to sites of inflammation. Diarrhea is the most common gastrointestinal side effect of MMOF usage with up to 40% of renal transplant patients on MMOF reporting this symptom and colonoscopy not infrequently shows injurious changes that range from edema and erythema to ulcerations and diffuse colitis. Isolated reports note that colonic histopathology from patients on MMOF sometimes mimic graft-versus-host disease, inflammatory bowel disease, or ischemic colitis. However, there are very few cases that describe segmental colitis in MMOF patients. We present a rare case of a renal transplant patient presenting with MMOF-induced segmental colitis after 4 years of medication usage. A 52-year-old male with a history of native kidney end stage renal disease secondary to diabetic nephrosclerosis status post living unrelated kidney transplant 4 years ago from his wife presented to the emergency room for 1 week of intractable abdominal pain, vomiting, and diarrhea. His current transplant medications included atovaquone, tacrolimus, and mycophenolate mofetil. Lab work showed chronic pancytopenia with hemoglobin 10, MCV 85, platelets 58, BUN:Cr 87:5.6, and tacrolimus level 34.8. His last colonoscopy 7 years ago was unremarkable and the patient had never had an esophagogastroduodenoscopy (EGD) before. EGD while admitted showed significant erosive gastropathy with pathology showing the same. Sigmoidoscopy showed segmental colitis with punctate erythema and loss of vascularity up to the splenic flexure with the distribution of mucosal disruption suggestive of ischemic colitis. Histopathology showed fragments of colonic mucosa with patchy active cryptitis, surface erosion, distorted crypts with concurrent apoptosis and scattered eosinophils in the lamina propria – findings consistent with mycophenolate colitis. Symptomatic care was provided and the patient's mycophenolate was tapered to cessation with complete resolution of symptoms. He was discharged with appropriate follow-up. Our case highlights a rare presentation of MMOF-induced injury whereby despite, appearance on endoscopy as a segmental ischemic colitis, histopathology was negative for ischemia but notable for MMOF-induced injury which was confirmed by symptom resolution following discontinuation of the immunosuppressive drug.. With early recognition of this pathology by clinicians with subsequent MMOF discontinuation, symptoms and prognosis can be remarkably improved. Colonoscopic image showing segmental colitis with punctate erythema and loss of vascularity. Fragments of colonic mucosa with patchy active cryptitis (star), surface erosion, mildly distorted crypts and apoptosis mainly in crypt bases with scattered eosinophils in the lamina propria, indicative of mycophenolate colitis. 400x magnification.